(untitled) (INNOVATIVE ECONOMY, 2024)
Bachynskyi V.I., Pomulіeva V.M. TAX DECLARATION ON INCOME TAX: PROBLEMS OF FORM AND CONTENT Purpose. The aim of the article is to study the actual problems of the form and content of the income tax return and search for ways to improve them. Methodology of research. General scientific and specific methods were used in the research: logical analysis, systemic approach, synthesis, induction and deduction, theoretical generalization and grouping, abstract and logical – when generalizing theoretical propositions and forming conclusions and proposals. Findings. Changes to the declaration form for the period of martial law are analysed and summarized. Attention is focused on the importance of submitting annexes to the declaration, in particular financial reporting. The actual problems of submitting financial statements to the controlling body as part of the income tax return are substantiated. Common errors in filing income tax returns are analysed and summarized, tax consequences and possible ways to prevent errors are determined. Proposals regarding the improvement of the income tax declaration process are formulated. The necessity and directions for its simplification are proposed and substantiated. Originality. The urgent need to simplify the income tax declaration process for taxpayers is substantiated, and proposals for its improvement are developed, which will ensure a reduction in the amount of time spent by taxpayers on preparing and submitting reports and avoiding errors and risks. This, in turn, will contribute to the reliability of tax reporting and the correctness of calculations with the budget. Practical value. The obtained research results and developed proposals can be used for further scientific research, in the development of regulatory documents and implemented through legislative changes, as well as by income tax payers in the preparation and submission of income tax returns. Key words: Tax Code, reporting period, tax declaration, corporate income tax, tax obligations, financial reporting.